2020
DOI: 10.3390/molecules25163699
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of an In Vivo Anti-Inflammatory Activity of Oleanolic Acid through Glycosylation Occurring Naturally in Stauntonia hexaphylla

Abstract: Stauntonia hexaphylla (Lardizabalaceae) has been used as a traditional herbal medicine in Korea and China for its anti-inflammatory and analgesic properties. As part of a bioprospecting program aimed at the discovery of new bioactive compounds from Korean medicinal plants, a phytochemical study of S. hexaphylla leaves was carried out leading to isolation of two oleanane-type triterpene saponins, 3-O-[β-d-glucopyranosyl (1→2)-α-l-arabinopyranosyl] oleanolic acid-28-O-[β-d-glucopyranosyl (1→6)-β-d-glucopyranosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Leaves of Stauntonia hexaphylla afforded two bioactive oleanane‐type triterpene saponins 226 and 227 . Their antiinflammatory activities were evaluated and both compounds exerted an inhibition of macrophage activation (Vinh et al, 2020).…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaves of Stauntonia hexaphylla afforded two bioactive oleanane‐type triterpene saponins 226 and 227 . Their antiinflammatory activities were evaluated and both compounds exerted an inhibition of macrophage activation (Vinh et al, 2020).…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
“….Leaves of Stauntonia hexaphylla afforded two bioactive oleananetype triterpene saponins 226 and 227. Their antiinflammatory activities were evaluated and both compounds exerted an inhibition of macrophage activation(Vinh et al, 2020).Araloside C (228), a saponin extracted from Aralia elata, had a protective effect on macrophage polarization in investigated atherosclerosis. The results showed that this compound significantly reduced the plaque area in atherosclerotic mice and the accumulation of lipids in ox-LDL-treated macrophages, promoted M2 phenotype macrophage polarization, increased the number of autophagosomes, and modulated the expression of autophagy-related proteins mediated by Sirt1 (Y Luo, Lu, et al, 2020)…”
mentioning
confidence: 99%
“…Cell cytotoxicity was evaluated using the 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. The cytotoxicity activity was assayed according to previously reported methods with slight modification (Vinh et al 2020). Briefly, RAW264.7 cells suspended in DMEM medium (10% FBS) were seeded onto a 96-well culture plate at a density of 5 x 10 3 cells/100 μL.…”
Section: Cytotoxicity Assay Using Mttmentioning
confidence: 99%
“…Fifty adult Wistar rats were of both sexes, with no pregnancies, and weights of 200 ± 20 g. The healthy, agile, and fluffy animals were kept in stainless steel cages in rooms maintained at 25 • C on 12-h light/dark cycles and provided free access to standard diet and water. The experimental procedures were approved by the Animal Ethics Committee and animal experiments were carried out per the approved protocols [8,10].…”
Section: Animalsmentioning
confidence: 99%
“…In order to isolate and evaluate the hepatoprotective effects of the extract of H. hirsuta, this study mainly studied the total methanol (MeOH) extract, which was the optimal extract to isolate most of the compounds present in the plant, and to evaluate the hepatoprotective effect [7,8,10]. However, traditional medicinal herbs are often used in the form of brandy immersion (equivalent to Ethanol: Water extract (1/1, v/v)).…”
Section: Introductionmentioning
confidence: 99%